The role of basic amino acid surface clusters on the collagenase activity of cathepsin K - Nallaseth, Ferez S. (Biochemistry, 2013)
Cathepsin K is a highly potent collagenase in osteoclasts and responsible for bone degradation. We have previously demonstrated that its unique collagenolytic activity is modulated by glycosaminoglycans that form high molecular complexes with the protease. However, mutational analysis of a specific glycosaminoglycan-cathepsin K binding site only led to a 60% reduction of the collagenolytic activity suggesting additional glycosaminoglycan binding sites or other determinants controlling this activity. We identified 8 cathepsin K specific arginine/lysine residues that form three positively charged clusters at the bottom part of the protease opposing the active site. These residues are highly conserved among mammalian, avian, and reptilian cathepsin K orthologues and to a lesser degree in amphibian and fish specimens. Mutational analysis of these residues revealed an approximately 50% reduction of the collagenolytic activity when the basic amino acids in cluster 2 (K106, K108, R108, R111) were mutated into alanine residues and resulted in a 100% loss of this activity when the mutations were expanded into cluster 3 (K122, R127). Cluster 1 mutations (K77, R79) had no effect. A partial rescue effect was observed when the hexa-mutant variant was combined with three mutations in the previously identified glycosaminoglycan binding site (N190, K101, L195K) indicating the relevance of at least two independent interaction sites. Amino acid substitutions in all sites had no effect on the catalytic efficacy of the protease variants as reflected in their unaltered peptidolytic and gelatinolytic activities and their overall protein stabilities. This study suggests that the basic amino acid clusters in cathepsin K are either involved in alternative glycoasaminoglycan binding sites, play other roles in the formation of collagenolytically active protease complexes or contribute in a yet unknown manner to the specific binding to collagen.